The Influence of Services and Digital Systems on Customer Satisfaction BSI Marelan - Muhammad Fadhil Al-Irsyad; Riyan Pradesyah (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2023)
The purpose of this study was to determine the effect of digital services and systems on customer satisfaction. Basically, currently, there are many digital systems that can harm customers, due to a lack of understanding of digital systems in the banking world. Therefore, researchers conducted research related to services, digital systems, and customer satisfaction. This research is quantitative research, the analytical tool used is SPSS. The tests used in the study include the classic assumption test, normality test, hypothesis test, and Rsquared test. The results obtained that the service variable affects the satisfaction of BSI customers, and the digital system variable affects the satisfaction of BSI customers, with a degree of freedom of 0.05. Simultaneously service variables and digital systems affect customer satisfaction BSI KCP Marelan, amounting to 44.6% and the remaining 55.4%, while other variables outside the study.